The implementation strategy of juvenile criminal law and its impact on juvenile recidivism prevention programs - Wilsa, Wilsa (Jurnal Konseling dan Pendidikan, 2025)
The implementation of juvenile criminal law plays a vital role in shaping the rehabilitation and prevention strategies for juvenile offenders. This study examines the effectiveness of current juvenile criminal law strategies and their impact on juvenile recidivism prevention programs. It explores how legal frameworks designed for minors differ from adult criminal law, focusing on their rehabilitative goals and the methods used to reintegrate young offenders into society. The research also delves into the various prevention programs aimed at reducing repeat offenses among juveniles, analyzing their outcomes and identifying key factors that contribute to success or failure. The findings highlight the importance of a tailored approach that considers the unique psychological and social needs of juveniles, advocating for an integrated strategy that combines legal, educational, and psychological support. By evaluating the impact of juvenile criminal law implementation, the study provides recommendations for enhancing prevention programs, emphasizing the need for systemic reforms, improved resources, and a more comprehensive approach to juvenile justice. Ultimately, this research underscores the significance of a balanced, rehabilitative legal system in reducing juvenile recidivism and fostering long-term societal benefits.